Thesis and antithesis: Resolving the dialectique in the first movement of Debussy’s Violin Sonata - Evans, Tristian (Interdisciplinary Studies in Musicology, 2018)
This article will offer a close reading of the first movement of Debussy’s Violin Sonata (1917), and will set forth to discuss its formal principles within a dialectical context. References to Hegelian philosophy will be made, and also to precursory dialectical structures. The work will also be studied in relation to sonata form, and by taking Mark DeVoto’s claim that this late work displays a “persuasive sonata form” structure into consideration, this analysis will in fact elucidate Debussy’s ostensible departure from archetypical sonata form. Examining Debussy’s correspondences and sketches will posit the Sonata initially within existing scholarship - both historiographical and analytical — paying particular attention to the composer’s “late” style in general. A discussion on the relationship between dialectic and symbolist aesthetics will then be necessary in order to promote the idea that the work is structured around a dialectical framework. The second section of this article will carry out an in-depth analysis of the movement, adopting and adapting a semiotic approach as developed by Nicolas Ruwet and Jean-Jacques Nattiez’s distributional methodology in order to study the work’s formal attributes and motivic construction. Use of this approach will bring to light the strong bond between the motivic thesis and antithesis in the first section of the Sonata, and also the conflation of material in the final section of the movement, which aims towards a dialectical resolution. Use of paradigmatic diagrams will illuminate the methods in which synthesis is achieved by different compositional strategies, including merging, completion, compression, combination and conjunction. Furthermore, the analysis will draw attention to Golden Section proportions in the middle section of the piece. In conclusion, it will be argued that Debussy’s conscious effort to avoid Teutonic principles has paradoxically brought his work closer to Germanic thinking. Amid a time of personal and social conflict, one could ultimately compare his approach to that of the Hegelian “free spirit” — a free spirit that transcends political boundaries by its occupation of a neutral ground. Whether or not this demonstrated Debussy’s conscious compositional intention to reflect Hegel’s philosophical principles remains unsolved. More certain, however, is the fact that the presentation of a thesis and a subsequent antithetical section clearly leads to a resolution of the dialectique in the first movement of this Sonata.